2014
DOI: 10.1080/01446193.2013.874565
|View full text |Cite
|
Sign up to set email alerts
|

Developing and evaluating a framework for process improvement in an alliance project: a New Zealand case study

Abstract: Lean thinking' holds out the promise of dramatic improvements in construction production processes, especially in waste minimization. While there exist empirical studies of 'leanness' with regard to non-relational-type projects, there is a need to analyse its applicability in relational contexts, such as an alliance. The application of 'lean' to a project alliance in a viaduct replacement in New Zealand is investigated here. The primary objective is to define a framework to streamline improvements in processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Lean construction researchers, on the other hand, have always maintained that lean construction principles and techniques are best implemented under a relational contractual framework (Vilasini et al 2014;Mathews and Howell, 2005). However, in practice, most construction projects are procured using other methods and arrangements such as a traditional design, bid, build; design and build; management contracting; and construction management; among others (especially in the UK and other Commonwealth countries).…”
Section: Last Planner System Implementation and Procurement Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lean construction researchers, on the other hand, have always maintained that lean construction principles and techniques are best implemented under a relational contractual framework (Vilasini et al 2014;Mathews and Howell, 2005). However, in practice, most construction projects are procured using other methods and arrangements such as a traditional design, bid, build; design and build; management contracting; and construction management; among others (especially in the UK and other Commonwealth countries).…”
Section: Last Planner System Implementation and Procurement Methodsmentioning
confidence: 99%
“…This finding aligns with a previous study in New Zealand that shows that collaborative procurement such as design and build could support the implementation of the LPS on a construction project (Fuemana et al 2013). Additionally, Vilasini et al, (2014) found that procurement methods with some collaborative undertone are the best to adopt in the implementation of lean construction techniques.…”
Section: Influence Of Dandb Procurement System On Look Ahead and Make-rmentioning
confidence: 99%
See 1 more Smart Citation
“…Although frequently implemented in the manufacturing and business worlds, the use of Six Sigma methodologies has been shown to be an effective approach in construction research (Banawi 2013;Koziolek and Derlukiewicz 2012;Lee and Su 2013;Mahasneh 2014;Paslawski 2013;Vilasini et al 2014).…”
Section: "Design and New Product Development Often Involves Qualitatimentioning
confidence: 99%
“…Further, management practices that are proven success in other fields (e.g. lean principles) were adapted to reflect construction project characteristics and applied successfully (Vilasini, Neitzert and Rotimi, 2014). Notwithstanding the essence of such developments, the efficiency of planning algorithms requires significant enhancement too (Fallah, Ashtiani and Aryanezhad, 2010).…”
Section: Introductionmentioning
confidence: 99%